2019
DOI: 10.1002/glia.23718
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes enhance glioblastoma growth

Abstract: Glioblastoma (GBM) is a deadly disease with a need for deeper understanding and new therapeutic approaches. The microenvironment of glioblastoma has previously been shown to guide glioblastoma progression. In this study, astrocytes were investigated with regard to their effect on glioblastoma proliferation through correlative analyses of clinical samples and experimental in vitro and in vivo studies. Co‐culture techniques were used to investigate the GBM growth enhancing potential of astrocytes. Cell sorting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
(47 reference statements)
1
43
0
1
Order By: Relevance
“…Tumor-associated astrocytes react to the GBM microenvironment with an altered phenotype, 60 and were recently shown to promote glioma growth. 32,61 We show here that astrocytes secrete TGM2 in response to radiation, which supports stemness and radiation resistance of GBM cells. Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Tumor-associated astrocytes react to the GBM microenvironment with an altered phenotype, 60 and were recently shown to promote glioma growth. 32,61 We show here that astrocytes secrete TGM2 in response to radiation, which supports stemness and radiation resistance of GBM cells. Inhibition of TGM2 decreased survival of tumor cells in an ex vivo organotypic slice model of GBM, and was previously shown to increase survival in a glioma xenograft model.…”
Section: Discussionsupporting
confidence: 57%
“…31 Several of these cell types have been shown to actively contribute to glioma aggressiveness. 32,33 Little is known about how these cells respond to radiotherapy, and how they in turn might affect the associated glioma cells after irradiation. We sought to determine whether irradiation of the brain tumor microenvironment might affect the phenotype and therapeutic response of glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…They also displayed a new potential role of microglia in glioblastoma: microglia appear to modulate sensitivity to cytotoxic agents conferring drug resistance to the tumor. Similarly, another study hypothesizes that astrocytes in TME behave like microglia by reducing cancer sensitivity to drugs and interactions between astrocytes and GB cells could be associated with increased growth and invasion of the tumor [96]. To confirm this, it was demonstrated that the direct contact between 3D co-culture of astrocytes and GB cells enhances glioblastoma formation [97].…”
Section: Co-cultures Of Cerebral Organoidsmentioning
confidence: 96%
“…Indeed, soluble DLK1 secreted from astrocytes was recently shown to be a critical component of the subventricular zone neural stem cell niche [11] . Astrocytes represent a prominent cell type in the brain tumor microenvironment [17] , and recent studies revealed that DLK1 is one of the top upregulated genes in tumor-associated astrocytes of high-grade vs low-grade gliomas [18] . The regulation of DLK1 expression is poorly understood, but some elements of the brain tumor microenvironment such as hypoxia have been shown to drive DLK1 expression [19 , 20] .…”
Section: Introductionmentioning
confidence: 99%